The wee free men eaudiobook - Pratchett, Terry (Discworld, 2004)
ALA Best Fiction for Young Adults * ALA Notable Children's Book * Horn Book Fanfare Book * Kirkus Reviews Editor's Choice * SLJ Best Book of the Year By the beloved and bestselling grandmaster of fantasy, Sir Terry Pratchett, this is the first in a series of Discworld novels starring the young witch Tiffany Aching. A nightmarish danger threatens from the other side of reality. . . . Armed with only a frying pan and her common sense, young witch-to-be Tiffany Aching must defend her home against the monsters of Fairyland. Luckily she has some very unusual help: the local Nac Mac Feegle—aka the Wee Free Men—a clan of fierce, sheep-stealing, sword-wielding, six-inch-high blue men. Together they must face headless horsemen, ferocious grimhounds, terrifying dreams come true, and ultimately the sinister Queen of the Elves herself. . . . The five funny and fabulous Tiffany Aching adventures are: The Wee Free Men A Hat Full of Sky Wintersmith I Shall Wear Midnight The Shepherd's Crown Tiffany's mentors, Granny Weatherwax and Nanny Ogg, star in the novels Equal Rites, Wyrd Sisters, Witches Abroad, Lords and Ladies, Maskerade, and Carpe Jugulum. And don't miss Terry Pratchett's hilarious and wise Discworld novel The Amazing Maurice and His Educated Rodents, winner of the Carnegie Medal!